KEADILAN DISTRIBUTIF DAN KOMITMEN ORGANISASIONAL SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN - Arista, Made Yudi; Suartana, I Wayan; Budiasih, IGA Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
Budget used by local government of Denpasar as an instrument of accountability in the area of ??financial management systems as well as basic public services. This research was conducted in the regional work units (SKPD) in Denpasar. This study aimed to examine the effect of budgetary participation on budgetary slack with distributive justice and organizational commitment as moderating. Methods of data collection in this study using survey method with a questionnaire measuring instrument. The number of samples in this study was 269 echelons of all SKPD in Denpasar chosen by purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that the budgeting participation give positive influence on budgetary slack. Distributive justice able to weaken the effect of budgetary participation on budgetary slack. . Organizational commitment is also able to weaken the effect of budgetary participation on budgetary slack.
Keywords: budgeting participation, distributive justice, organizational commitment, budgetary slack